Analysis of indoor environment perceptions in the smart building. Issue 1 (1st September 2022) - Krawczyk, N; Wojciechowska, P
Abstract: Thermal comfort is of fundamental importance for people staying in a closed environment. The article focuses on research on thermal comfort in a smart building. The study was performed using two methods. The first method with the Testo 400 microclimate meter, the second method with anonymous questionnaires. The microclimate meter made it possible to measure air parameters (including temperature, humidity, speed, CO2 concentration). The anonymous poll included questions about the thermal sensations vote, thermal preferences, thermal acceptability vote, air humidity and humidity preferences vote. Students from Poland, faculty of Environmental, Geomatic and Energy Engineering, participated in the study. The research showed that the respondents preferred lower thermal conditions with the temperature range from 22.4 °C to 25.1 °C. The percentage of the students who found the conditions as unsatisfactory - has exceeded the permitted 10% range.